Searches for third-generation scalar leptoquarks in s√=13 TeV pp collisions with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Journal of high energy physics, 2019)
Limits are set on the pair production of scalar leptoquarks, where all possible decays of the leptoquark into a quark (t, b) and a lepton (τ, ν) of the third generation are considered. The limits are presented as a function of the leptoquark mass and the branching ratio into charged leptons for up-type (LQ 3 u → tν/bτ) and down-type (LQ 3 d → bν/tτ) leptoquarks. Many results are reinterpretations of previously published ATLAS searches. In all cases, LHC proton-proton collision data at a centre-of-mass energy of s√s \sqrt{s} = 13 TeV recorded by the ATLAS detector in 2015 and 2016 are used, corresponding to an integrated luminosity of 36.1 fb−1. Masses below 800 GeV are excluded for both LQ 3 u and LQ 3 d independently of the branching ratio, with masses below about 1 TeV being excluded for the limiting cases of branching ratios equal to zero or unity. Open image in new window